The Rise and Fall of the People's Parties A History of Democracy in Western Europe since 1918 - Corduwener, Pepijn (Oxford University Press, 2023)
The decline of the centre-left and centre-right people's parties is arguably the most poignant feature of the crisis of democracy in Western Europe today. To understand why, this book explores the striking parallels between the life of democracy and that of the people's parties over the course of the past century. It offers a transnational window on the history of democracy since 1918 by weaving together three epochs which are often studied apart: democracy's troubled history in the Interwar era; the trente glorieuses after the Second World War; and the period since the 1970s. The book shows that democracy was only stabilized and legitimized when people's parties emerged that managed to balance between facilitating popular participation from below, bridging divisions between social groups, and practising the politics of compromise. Ideas for such parties existed already in the first decades of the twentieth century. Nonetheless, Socialist and Catholic mass parties failed to transform into people's parties, which was essential for the crisis (and breakdown) of democracy in the Interwar era. This was a traumatic experience which contributed to the unexpected stabilization of democracy after 1945 as party leaders transformed their organizations into broad-based people's parties that embraced compromise and responsibility. However, this stability did not last, and paradoxically their transformation also harboured the seeds of democracy's more recent problems. Over the past decades, people's parties have struggled to connect to an individualizing society while having become increasingly absorbed by their governing responsibilities.